Diagnosis and treatment of latent tuberculosis infection among household contacts in inland Bahia, Brazil: a cross-sectional follow-up study - Guilherme Lages Matias; Marcio Vinicius Ferreira Sales; Gabriela Santos Andrade; Brenda dos Santos Teixeira; Maria Eduarda da Macena Tenorio; Maria Augusta Vasconcelos Palácio; Maria Luisa de Carvalho Correia; Iukary Takenami (São Paulo Medical Journal)
ABSTRACT BACKGROUND: The diagnosis and treatment of latent tuberculosis infection (LTBI) are crucial for tuberculosis (TB) control. Household contacts (HHC) of patients with pulmonary TB are at a high risk of LTBI due to their close proximity to source cases. OBJECTIVE: To describe the diagnosis and treatment of LTBI among HHC. DESIGN AND SETTING: This cross-sectional follow-up study was conducted in the municipality of Paulo Afonso, northeastern Brazil, between 2013 and 2022. METHODS: We retrieved secondary data from the medical records of HHC who were followed up at a specialized referral center for TB. LTBI prevalence estimates were calculated and are presented with 95% confidence intervals (CIs). RESULTS: In total, 622 HHC were screened for LTBI, with 620 evaluated using the tuberculin skin test (TST). Of these, 40 (6.5%) did not return for TST reading. The overall prevalence of LTBI was 53.1% (95% CI: 49–57.1%), with a high prevalence among females and individuals aged 25–34 years. The overall LTBI treatment initiation rate was 26.1% (95%CI: 21.5–31.3%), and 64.2% (95%CI: 53.3–73.8%) of HHC who initiated treatment completed their course. CONCLUSION: This study revealed a high prevalence of LTBI among HHC, particularly among women and individuals aged 25–34 years, underscoring the ongoing TB transmission within the community. Only 26.1% of the diagnosed HHC initiated treatment, with approximately 64% completing their course. This highlights the challenges in managing LTBI and emphasizes the need for targeted screening and interventions for high-risk groups.